Fleksibilitas Manajerial, Penganggaran Agile, dan Reposisi Slack Anggaran dalam Sistem Akuntansi Manajemen - Setiajatnika, Eka; Buana, Surya Pancar (Coopetition : Jurnal Ilmiah Manajemen, 2026)
The increasingly intense dynamics and uncertainty of the business environment challenge the relevance of traditional budgeting systems in management accounting, particularly in manufacturing companies within the consumer goods sector. During the 2020–2024 period, this sector faced efficiency pressures, performance fluctuations, and recurring misalignments between budgets and actual outcomes, reflecting the limitations of rigid budgeting practices. This study aims to analyze the role of managerial flexibility in the formation of budgetary slack and to examine agile budgeting as a moderating mechanism within management control systems. The research employs a quantitative explanatory approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) on a sample of 80 consumer goods manufacturing companies listed on the Indonesia Stock Exchange. Data were collected from annual financial statements and surveys of financial and accounting managers. The results indicate that managerial flexibility has a positive effect on functional budgetary slack, and that agile budgeting strengthens this relationship. These findings suggest that budgetary slack can function as an adaptive mechanism when managerial behavior aligns with the design of a responsive budgeting system. Keywords: managerial flexibility; budgetary slack; agile budgeting; management control systems; management accounting.